Coulomb explosion of powders under fast pressure decrease. (May 2023) - Yarygin, I.V.; Yarygin, V.N.; Prikhodko, V.G.; Fedoseev, A.V.; Maltsev, V.A.; Novopashin, S.A.
Abstract: A phenomenon of spontaneous expansion of dielectric particles with a decrease in pressure in a vacuum chamber is experimentally studied. There is a certain range of ambient pressure and pressure decreasing rate at which the phenomenon is observed. The experiments show that the phenomenon relates weakly to gas dynamics, influence of wall material and particle surface desorption. It is established that the Coulomb repulsion of charged particles causes this effect. Highlights: Expansion of powder particles under a rapid decrease in ambient pressure is found. The phenomenon is electrical in nature and represents new type of Coulomb explosion. The phenomenon occurs at a certain pressure level and pressure decreasing rate.